Flute solos: whit piano acompaniment - Arnold, Jay (Everybody's Favorite Series, 1940)
We take pride in presenting what we believe to be the most diversified group of Flute solos ever assembled in one volume. The many melodious compositions bring out the beautiful singing quality of the instrument, while other numbers take advantage of the suitability for passages requiring considerable technical facility.